Incorporation of sterols into ram sperm reduces the percentage of acrosome reacted spermatozoa after cryopreservation - Carro, Maria de Las Mercedes (2017)
Cryopreservation of sperm is a useful biotechnological tool for artificial insemination. However, ram sperm is particularly sensiti- ve to this process, limiting its use for this species. Previously, we found a significant sterol loss in cryopreserved ram sperm and a concomitant decrease in membrane lipid order. Recently, we esta- blished controlled conditions to increase sperm sterol content using methyl-β-cyclodextrin (MβCD). The objective of this study was to evaluate the impact of increasing cholesterol (Chol) and desmoste- rol (Des) content of ram sperm (2.5, 10, 25mM MβCD-sterol) on: 1) membrane lipid order and level of the putative raft marker, ganglio- side GM1 , and 2) sperm quality parameters after thawing. Treatment of semen with 10 and 25mM MβCD-Chol or -Des increased mem- brane lipid order determined by fluorescence spectroscopy (Laur- dan). The presence of GM1 was detected in living sperm using the fluorescent-labeled cholera toxin B subunit. GM1 -related fluorescen- ce was mainly associated to the post-acrosomal region and was re- duced when both sterols were incorporated into the sperm at 25mM MβCD, suggesting a membrane disorganization effect induced by sterol incorporation (p<0.05). Therefore, 10mM concentration was selected to incorporate sterols into ram sperm prior to cryopreser- vation. As to the sperm quality parameters analyzed, no significant differences were found in percentages of total motility, membrane integrity (eosin/nigrosin) and osmotic tolerance (HOS test) between control and treated cells, irrespective of the class of sterol. Howe- ver, the percentage of acrosome reacted sperm evaluated by con- canavalin A staining after cryopreservation was reduced by sterol incorporation (p<0.05). We conclude that treatment of ram sperm with 10mM MβCD, complexed either with Chol or Des, increases membrane lipid order without affecting GM1 -related raft organization and exerts a stabilizing effect of the acrosome reducing acrosome reaction induced by cryopreservation.